2016
DOI: 10.1186/s40068-016-0063-4
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorus pesticide residues in soils and drinking water sources from cocoa producing areas in Ghana

Abstract: Background: Pests and diseases are recognised as major factors responsible for the decline in cocoa yield in Ghana. This has resulted in an increased use of pesticides to increase productivity. The regular application and indiscriminate use of chemicals have been associated with unintended environmental and human health consequence. The objective of this study was to determine levels of 13 organophosphorus pesticide residues in soils and drinking water sources in and around cocoa farms in Brong Ahafo region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 20 publications
0
26
4
1
Order By: Relevance
“…Research conducted by Fosu-Mensah et al also found residuals of chlorpyrifos and profenofos in soil samples on cultivated cocoa farms in Ghana [6]. Supriyadi et al also conducted a study to determine the presence of organophosphate residues in agricultural land located in mojogedang, karanganyar central java province.…”
Section: Resultsmentioning
confidence: 99%
“…Research conducted by Fosu-Mensah et al also found residuals of chlorpyrifos and profenofos in soil samples on cultivated cocoa farms in Ghana [6]. Supriyadi et al also conducted a study to determine the presence of organophosphate residues in agricultural land located in mojogedang, karanganyar central java province.…”
Section: Resultsmentioning
confidence: 99%
“…According to Gerken et al (2001), the improper disposal of empty pesticide containers, unwanted pesticides or left over spray solutions may lead to contamination of soil in the farm and environment by runoff, leaching or aerial distribution to other areas. Fosu-Mensah et al (2016) reported four organophosphorus pesticide residues (chlorpyrifos, profenofos, pirimiphos-methyl and diazinon) in soil and water samples from cocoa farms in the study area which is an indication of soil and water pollution. The Environmental Health Manual (2010) identifies the community rubbish damp as the best place to discard empty pesticides containers after being wash three times with the appropriate solvent.…”
Section: Washing Of Personal Protective Equipment (Ppe) After Pesticimentioning
confidence: 97%
“…For example, in Ghana CPF (0.01-0.04 mg/kg), profenofos (0.02-0.04 mg/kg) and pirimiphos-methyl (0.01-0.04 mg/ kg) residues were detected in soil samples, while OP residues recorded in the water samples were CPF, 0.01-0.05 µg/L; diazinon, 0.01-0.04 µg/L, and pirimiphos-methyl, 0.01-0.03 µg/L. The concentration of CPF and diazinon residues exceeded their respective values according to the WHO guidelines for drinking water (Fosu-Mensah et al 2016).…”
Section: Resultsmentioning
confidence: 78%